Being mortal : medicine and what matters in the end - Gawande, Atul (New York : Metropolitan Books/Henry Holt and Company, 2014)
Atul Gawande tackles the hardest challenge of his profession: how medicine can not only improve life but also the process of its ending. Full of eye-opening research and riveting storytelling, Gawande asserts that medicine can comfort and enhance our experience even to the end, providing not only a good life but also a good end.
The independent self -- Things fall apart -- Dependence -- Assistance -- A better life -- Letting go -- Hard conversations -- Courage.
Includes bibliographical references.
Keywords: Terminal care; Critical care medicine; Aging -- Physiological aspects; Prognosis; Quality of life